Causal role of immune cells in thyroid cancer: a bidirectional Mendelian randomization study - Fang, Xianliu; Huang, Xiaoxiao; Lu, Jianhua; Su, Danke (Frontiers in Immunology, 2024)
Background:The immune system plays an important role in the development and treatment of thyroid cancer(THCA).However, the correlation between immune cells and THCA has not been systematically studied.Methods:This study used a two-sample Mendelian randomization (MR) study to determine the causal relationship between immune cell characteristics and THCA.Based on a large sample of publicly available genetic data, we explored the causal relationship between 731 immune cell characteristics and THCA risk.The 731 immunophenotypes were divided into 7 groups,including B cell panel(n=190),cDC panel(n=64),Maturation stages of T cell panel(n=79) ,Monocyte panel(n=43),Myeloid cell panel(n=64),TBNK panel(n=124),and Treg panel(n=167). The sensitivity of the results was analyzed, and heterogeneity and horizontal pleiotropy were excluded. Results:After FDR correction, the effect of immunophenotype on THCA was not statistically significant. It is worth mentioning, however, that there are some unadjusted low Pvalues phenotypes.The odds ratio (OR) of CD62L on monocyte on THCA risk was estimated to be 0.953 (95% CI=0.930~0.976, P=1.005×10 -4 ),and which was estimated to be 0.975(95% CI=0.961-0.989, P=7.984×10 -4 ) for Resting Treg%CD4 on THCA risk.Furthermore,THCA was associated with a reduced risk of 5 immunophenotype:CD25 on CD39+ CD4 on Treg (OR=0.871, 95% CI=0.812~0.935,